KUALITAS LAYANAN AI TOOLS DAN RELIGIUSITAS: DAMPAK TERHADAP NIAT PEMBELIAN ONLINE SHOPPING PADA KONSUMEN MUSLIM - Inas Afifah Zahra; Rika Lisnawati; Sandhika Cipta Bidhari (Media Riset Bisnis Ekonomi Sains dan Terapan, 2026)
This study examines the impact of AI Tools service quality, represented by response accuracy, consistency, and technology quality, on online shopping purchase intention among Muslim consumers, with religiosity serving as a moderating variable. The increasing adoption of artificial intelligence in e-commerce has enhanced customer service and shopping experiences; however, limited research has explored its effectiveness in influencing purchase intention among Muslim consumers. This study employed a quantitative approach using a survey of 100 Muslim consumers in the Greater Jakarta area (Jabodetabek), Indonesia. Data were collected through an online questionnaire and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicate that response accuracy has a positive and significant effect on purchase intention, while consistency and technology quality do not significantly influence purchase intention. Furthermore, religiosity does not moderate the relationships between response accuracy, consistency, technology quality, and purchase intention. These findings suggest that Muslim consumers place greater emphasis on the accuracy and relevance of information provided by AI Tools than on technological sophistication or personal religiosity when making online purchasing decisions.Keywords: AI Tools Service Quality, Muslim Consumers, Online Shopping, Purchase Intention, Religiosity